‘I’m trying to tell you this man is dangerous… and no one’s listening’: Family violence, parent–school engagement and school complicity - Ayre, Kay (2021)
© 2020, The Author(s). This paper presents a case study of one mother’s experience of engaging with her children’s schools after leaving a long-term relationship characterised by years of family violence perpetrated by the children’s father. We interviewed Bernadette as part of an ongoing study of parents’ experiences of school engagement during family separation and divorce. Her family circumstances and the role the children’s schools played in that story merit consideration by educators, school leaders and education policy makers. Informed by theories of everyday cultural practices and sociological studies of gendered power relations in education, we argue that gender politics and organisational strategies for keeping parents ‘in their place’ can significantly contribute to systemic failures and school cultures that reinscribe the effects of family violence